Tellurium Compound AS101 Ameliorates Experimental Autoimmune Encephalomyelitis by VLA-4 Inhibition and Suppression of Monocyte and T-Cell Infiltration into the CNS - Lee, Jun-Ho (2013)
Multiple sclerosis (MS) is an inflammatory autoimmune disease of the central nervous system (CNS) involving demyelinating and neurodegenerative processes. Several of the major pathological CNS alterations and behavioral deficits of MS are recapitulated in the experimental autoimmune encephalitis (EAE) mouse model in which the disease process is induced by administration of myelin peptides. Development of EAE requires infiltration of inflammatory cytokine-generating monocytes and macrophages, and auto-reactive T cells, into the CNS. Very late antigen-4 (VLA-4, α4β1) is an integrin molecule that plays a role in inflammatory responses by facilitating the migration of leukocytes across the blood-brain barrier during inflammatory disease, and antibodies against VLA-4 exhibit therapeutic efficacy in mouse and monkey MS models. Here we report that the tellurium compound AS101 (ammonium trichloro (dioxoethylene-o,o’) tellurate) ameliorates EAE by inhibiting monocyte ant T-cell infiltration into the CNS. CD49d is an alpha subunit of the VLA-4 (α4β1) integrin. During the peak stage of EAE, AS101 treatment effectively ameliorated the disease process by reducing the number of CD49d+ inflammatory monocyte/macrophage cells in the spinal cord. AS101 treatment markedly reduced the pro-inflammatory cytokine levels, while increasing anti-inflammatory cytokine levels. In contrast, AS101 treatment did not affect the peripheral populations of CD11b+ monocytes and macrophages. AS101 treatment reduced the infiltration of CD4(+) and CD49(+)/VLA4 T cells. In addition, treatment of T cells from MS patients with AS101 resulted in apoptosis, while such treatment did not affect T cells from healthy donors. These results suggest that AS101 reduces accumulation of leukocytes in the CNS by inhibiting the activity of the VLA-4 integrin, and provide a rationale for the potential use of Tellurium IV compounds for the treatment of MS.